Public perceived knowledge of, attitude toward, and use of genetic testing in urban China. Issue 6 (4th May 2021) - Wang, Qun; Pang, Cong; Meng, Lingyu; Wang, Guoyu
Abstract: Because most research about laypeople and genetic testing (GT) has been conducted in other nations than China, we conducted a study in urban China (a) to determine the perceived knowledge of, attitude toward, and use of GT there; (b) to identify influencing factors associated with the public's perceived knowledge, attitudes, and use of GT; and (c) to explore the relationship among public knowledge of, attitude toward, and use of GT. Our data came from a community‐based survey in urban Dalian of 868 individuals. We used generalized ordered logit and logit models to examine factors associated with perceived knowledge of, attitude toward, and use of GT. We found that 67% of community members knew about GT, that 45% had a positive opinion of GT, and that only 4% accessed GT. Older people were more likely to have less perceived knowledge of GT and less likely to have a negative attitude toward it; these relationships were especially stronger among those aged ≥60 years. We also found that socially disadvantaged people were more likely to have less perceived knowledge of GT and more likely to have a negative opinion of it. Having a greater level of perceived knowledge was significantly correlated with increased odds of having a more positive or neutral attitude toward GT and of being more likely to access GT. Our findings may help policy makers design effective action plans and regulations regarding GT and genetic counseling services for laypersons in China.